Etika Penggunaan Tes Inteligensi dalam Konseling : Pilar Profesionalisme dan Kemanusiaan - Devytha Maura A P (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This article explores the ethical principles in the use of intelligence tests in the field of counseling. As a diagnostic tool, intelligence tests provide important information about clients' cognitive potential. However, their implementation requires ethical awareness from counselors, including informed consent, data confidentiality, fairness, and cultural sensitivity. The study emphasizes the role of ethics in promoting responsible assessments and client well-being. Findings indicate that counselors who adhere to ethical standards deliver more accurate and supportive counseling interventions.